Intoxication after Extreme Oral Overdose of Quetiapine to Attempt Suicide: Pharmacological Concerns of Side Effects - C. Müller; H. Reuter; C. Dohmen (Case Reports in Medicine)
Quetiapine is an atypical antipsychotic approved for the treatment of patients with psychotic disorders. Since approvement several case reports about intoxication with quetiapine were linked mainly with tachycardia, QTc-prolongation, somnolence, and hyperglycemia. Here, we present the first case report of an intoxication with an extreme overdose of quetiapine (36 g), ingested by a 32-year-old female (62 kg bodyweight) to attempt suicide. Symptoms associated with intoxication were coma without arterial hypotension, persistent tachycardia, hyperglycemia, and transient hypothyreoidism. QTc-interval was moderately extended. Management consisted of intubation for airway protection, gastric lavage, the use of activated charcoal, i.v. saline, and observation for 17 hours on an intensive care unit. Despite the extremely high dose of quetiapine, the patient recovered completely without residual symptoms.